If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6w + 9 = 18w + -3w + 81 Reorder the terms: 9 + 6w = 18w + -3w + 81 Reorder the terms: 9 + 6w = 81 + 18w + -3w Combine like terms: 18w + -3w = 15w 9 + 6w = 81 + 15w Solving 9 + 6w = 81 + 15w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-15w' to each side of the equation. 9 + 6w + -15w = 81 + 15w + -15w Combine like terms: 6w + -15w = -9w 9 + -9w = 81 + 15w + -15w Combine like terms: 15w + -15w = 0 9 + -9w = 81 + 0 9 + -9w = 81 Add '-9' to each side of the equation. 9 + -9 + -9w = 81 + -9 Combine like terms: 9 + -9 = 0 0 + -9w = 81 + -9 -9w = 81 + -9 Combine like terms: 81 + -9 = 72 -9w = 72 Divide each side by '-9'. w = -8 Simplifying w = -8
| -2V+r=2k | | X-12y=-62 | | 0.5=-0.6ln(x)+1 | | y-49=-2 | | 86-2x=6-10x | | 1/x^3=0 | | 0=x-4+3x | | 1/x^3 | | 2xy+3z+1=0 | | x-3-8x-6= | | 5x-2=13x-19 | | 5w^2-30w+40=0 | | 80-5x+4x+10+80=180 | | -6(4y)= | | 6u+6(u-6)=36 | | 4x+10+80-5x=180 | | 13d^2-7d=0 | | -x+17y=127 | | 4(2x-1)-(-3+7)= | | 2y+9=4y-3 | | -1-7x=36x+6(-7-x) | | 4x^4y-36x^3y+80x^2y= | | (17+a)+12= | | x+3=x+11 | | 3z=6z-1 | | 2(-1-3x)=25+3x | | 4M-2(M+6)=5(3M-2)+6 | | 4+4(4x-4)=8-3(2x+1) | | 2y+2=-3 | | 5a-2+3a=17+12a-23 | | x^2-8x+64= | | Y=4Y^2-32Y+65 |